Ballooning technique for orbital floor fracture reduction in neglected midfacial fracture: a case report - Siauw, Cahyadi; Syamsudin, Endang; Ismiarto, Yoyos Dias (Hasanuddin University, 2019)
Objective: Midfacial fracture is a fracture that separates maxilla from the middle part of face. Orbital floor fracture includes in midfacial fracture that difficult to treat. The aggravating factor of the treatment are depressed fractures and infection. We use ballooning technique which is inflated in the maxillary sinus to lift fracture segment of orbital floor and to prevent the orbital floor displaced to the maxillary sinus.Methods: There were multiple lacerations at left eye and nose region, post suturing at left zygoma and left cheek region. Intraoral findings there were multiple laceration, then the patient was examined a complete blood count, chest xray, cervical lateral examination, and 3D CT-Scan examination.Results: Examination of head and panoramic xray was performed and showed there was no bone discontinuity, contact and stable fracture segments. Examination of the 5th day post operative showed minimal pus drainage, leukocytes were within normal limits and other lab results were normal. Physical examination showed minimum scar, there was no dehiscence, symmetrical face and drain was performed at left zygoma region, symmetrical orbital, intact and stable occlusion.Conclusion: In this case, ballooning technique was successfully reduced the ruptured orbital floor and obtained good result.Keywords: Ballooning, Fixation, Open fracture, Orbital floor fracture. Â